Primary malignant melanoma of the orbit arising in a cellular blue naevus. Issue 5 (May 1989) - Löffler, K U; Witschel, H
Abstract : Primary malignant melanoma of the orbit is a rare clinical entity. We report the clinical course and present the light and electron microscopic findings in a case arising in a cellular blue naevus. While most orbital melanomas are associated with a naevus of Ota, there was no clinically visible abnormal pigmentation in our patient. The possible origin of the tumour cell and its ultrastructural features are discussed.